Prospection for potential new non-ribosomal peptide gene clusters in Bacillus genus isolated from fermented foods and soil through genome mining - Waongo, Blaise; Ndayishimiye, Libère; Tapsoba, François; Zongo, Wend-Soo Abel; Li, Jinquan; Savadogo, Aly (Frontiers in Microbiology, 2025)
Experimental studies, though often very costly, lead to the discovery of known antimicrobial products. Yet, pathogenic microorganisms are proving increasingly resistant to pre-existing antimicrobial molecules, and this is a cause for worldwide concern. Therefore, it is necessary to search for new molecules that could serve as alternatives in the food, medical and agricultural sectors. Thus, 123 complete genomes of Bacillus strains isolated from soil and fermented foods were analyzed and annotated using bioinformatics prediction and characterization tools. The view was to discover new gene clusters for the biosynthesis of non-ribosomal peptides (lipopeptides, siderophores, antibiotics). This study revealed that 83% of the genomes analyzed possess biosynthetic gene clusters for the production of siderophore bacillibactin, 61% for surfactins, 37% for fengycins, 23% for iturins, 15% for kurstakins and 3% for bacitracin. Besides, seven new biosynthetic gene clusters coding Non Ribosomal Peptide Synthetases (NRPS) have been identified in B. velezensis ATR2, B. velezensis DSYZ, B. velezensis CGMCC11640, B. amyloliquefaciens HM618, B. amyloliquefaciens WF02, B. cereus CMCC P0011, B. cereus CMCC P0021, B. subtilis SJ-10 and B. anthracis CMF9. The results of this study revealed a significant potential of the genus Bacillus to produce new non-ribosomally synthesized peptides. Now, these predicted new antimicrobial molecules can be easily studied experimentally as many new gene clusters have been identified.